The nature of the copper sulfide film grown on copper in aqueous sulfide and chloride solutions. Issue 1 (5th June 2020) - Guo, Mengnan; Chen, Jian; Martino, Taylor; Lilja, Christina; Johansson, Johannes A.; Behazin, Mehran; Binns, Wilfred J.; Keech, Peter G.; Noël, James J.; Shoesmith, David W.
Abstract: In this paper, the properties of copper sulfide films formed both anodically and naturally in deaerated/anoxic aqueous sulfide and chloride solutions were investigated using a series of electrochemical and surface analytical techniques. A combination of cyclic voltammetric, corrosion potential ( E corr ), and cathodic stripping voltammetric experiments showed that the sulfide film growth kinetics and film morphologies were controlled by the supply of SH − from the bulk solution to the copper surface. There was no passive barrier layer observed on the copper surface under either electrochemical or corrosion conditions. The film morphology was dependent on the type and concentration of anions (SH −, Cl − ) present in the solution. Scanning electron microscopy on both surfaces and focused ion beam‐cut cross‐sections showed the growth of a thin, but porous, base layer of chalcocite (Cu2 S) after short immersion periods (up to 2 hr) and the continuous growth of a much thicker crystalline outer deposit over longer immersion periods (≥36 hr), suggesting a solution species transport‐based film formation process and the formation of an ineffective thin "barrier‐type" layer on copper. Abstract : Copper is the chosen material for spent nuclear fuel containers in Sweden, Finland, and Canada. Trapped oxygen in a deep geological repository will be rapidly consumed by mineral/microbial reactions, leaving SH −, produced remotely by the action of S O 4 2 − ‐reducing bacteria, as the major threat to container durability. This study focuses on the determination of the corrosion mechanism and the distribution of corrosion damage on containers with a copper coating or shell.